A taxonomy of the expected roles of librarians towards knowledge management: An eight-layer perspective for practice. Issue 1 (6th August 2018) - Abukhader, Sajed
Abstract : Purpose: The purpose of this paper is to explore the connection between the various layers of roles and tasks of librarians with the various knowledge types and methods. Although there are multiple benefits anticipated with knowledge management (KM) schemes in libraries, the practical side of it among Library and Information Science (LIS) professionals is not yet notable or evident. Design/methodology/approach: Taxonomy building and Delphi method were two means of research deployed to achieve the declared purpose. Findings: It was possible to achieve several steps into structuring a taxonomy but yet further work has to be accomplished in order to consummate the taxonomy. For this, means of group interviewing method along with perhaps sponsorship of association relevant to librarianship might be an appropriate approach. Research limitations/implications: Delphi process was not possible to be fully exercised and completed due to limitations of limited number of participants as well the overwhelming feeling of participants had toward the unfamiliar content. It would have been more rewarding to have physical meeting in groups to overcome such limitations. Originality/value: This paper lays the foundation stone of a multi-layer taxonomy for roles of librarians toward KM. The taxonomy also unveils a dimension that librarians often miss when discussing KM. It also models the categories of knowledge types for LIS. Thus, the LIS community is urged to contribute in the development of this taxonomy which could become the handbook of reference in KM for librarianship.